Thermodynamic properties of 2H-MoSe2 from first principles quasi-harmonic approximation - Vasiliev, O. (Physics and Chemistry of Solid State, 2020)
In this paper, we report the results of first-principles calculation of 2H-MoSe2 thermodynamic properties within the quasi-harmonic approximation. The focus of the article is on the temperature dependencies of the heat capacity up to 1000 ℃ and values of enthalpy of formation, enthalpy, and entropy at 298,15 K, and their comparative analysis with the existing experimental data. The results show good general agreement with the published experimental data sets allowing to use them as arbitration of existing discrepancies. Increasing deviations of the heat capacity above the room temperature suggest that factors not included in the quasi-harmonic approximation, such as vibrational anharmonicity, may have a significant influence on the thermodynamics of 2H-MoSe2 in this temperature region. Considering the inconclusive high-temperature data from the experiment, the present results may be recommended as a satisfactory approximation until the appearance of more reliable experimental data or calculation results, taking into account more finite-temperature effects.